Menelisik Permasalahan Motivasi Belajar Peserta Didik di Era Modern - ZA, In’am Isro’ati Marzuuqoh; Utari, Vero Esra; Rusika, Selvia; Pratama, Linardo (Indo-MathEdu Intellectuals Journal, 2025)
This article aims to analyze the learning motivation of students in the modern era, which has declined due to the development of digital technology, changes in lifestyle, and increasing distractions from various forms of entertainment. The research design is based on a literature study conducted by reviewing journal articles, scientific books, proceedings, research reports, and other credible publications. Data collection was carried out through stages of keyword identification, title and abstract screening, full reading, and noting key points. Data analysis was conducted using a content analysis approach. The study results indicate that low learning motivation is influenced by internal factors such as fatigue, stress, low self-confidence, and weak self-regulation skills, as well as external factors such as lack of family support, less varied teaching methods, and the use of technology that is more focused on entertainment. The impact of low motivation is evident in declining learning outcomes, increased boredom, low social participation, and reduced academic responsibility. This study emphasizes that efforts to enhance learning motivation need to be carried out comprehensively through positive reinforcement, creating a comfortable learning environment, appropriate use of technology, and collaboration between teachers, parents, and the school environment. These efforts are important to rekindle students' intrinsic motivation so that they can adapt and learn optimally in the modern era